Diet composition of Adélie Penguins Pygoscelis adeliae at Hope/Esperanza Bay during 2014-2019 - Silvestro, Anahí Mariel; Casaux, Ricardo Jorge
In this study, we obtained samples through stomach lavage to determine the diet of Adelie Penguins Pygoscelis adeliae during the guard and crèche periods at Hope/Esperanza Bay, Antarctica, during four breeding seasons (2014–2019, except 2016). Antarctic krill was the dominant prey, contributing > 99.6% of the diet by mass. The remainder of prey were fish, amphipods, and mollusks. Among fish, the nototheniid Pleuragramma antarcticum was the most frequent while the bathydraconid Parachaenichthys charcoti dominated by mass. Mollusks and fish increased their contribution during the crèche period in accord with seasonal patterns elsewhere. Fil: Silvestro, Anahí Mariel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Centro de Investigación Esquel de Montaña y Estepa Patagónica. Universidad Nacional de la Patagonia "San Juan Bosco". Centro de Investigación Esquel de Montaña y Estepa Patagónica; Argentina Fil: Casaux, Ricardo Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Centro de Investigación Esquel de Montaña y Estepa Patagónica. Universidad Nacional de la Patagonia "San Juan Bosco". Centro de Investigación Esquel de Montaña y Estepa Patagónica; Argentina